Land control dynamics and social-ecological transformations in upland Philippines. Issue 4 (4th July 2017) - Montefrio, Marvin Joseph F.
Abstract : Recent scholarship on land grabs has begun exploring the complexity of local dynamics of land control, with emphasis on the concepts of access and exclusion and the social processes that influence these two. In this paper, I emphasize that a nuanced examination of broader social-ecological transformations would enrich our understanding of land control and exclusion. Drawing from field research in the Philippine province of Palawan, this paper examines how the combined effects of the practices of conservation enclosures, the uneven land accumulation brought about by oil palm expansion, and the use of legitimizing upland discourses all contribute to social-ecological transformations in swidden and the exclusion of indigenous smallholders from benefiting from integral forms of swidden agriculture. These practices of land control and the associated social-ecological transformations are not just interconnected, but also characterized by feedback mechanisms. The more smallholders decide to alter (or abandon) swidden practices, participate in oil palm contract farming, and/or sell their land to oil palm growers, the greater the tendency for land to accumulate among migrant settlers and absentee landowners. This, in turn, may lead to further reduction in the availability of fallow land and exclusion of more indigenous smallholders over time.